2020
DOI: 10.12659/msm.922420
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lymph Node Ratio in Breast Cancer Patients with Adequate Pathologic Evidence After Neoadjuvant Chemotherapy

Abstract: Departmental sources Background:The prognostic role of axillary lymph node ratio (LNR) after neoadjuvant chemotherapy (NAC) in breast cancer has not been illuminated. This study was designed to investigate the prognostic role of LNR in breast cancer compared with traditional ypN stage. Material/Methods:A total of 306 breast cancer patients diagnosed with positive axillary lymph nodes from January 2007 to December 2014 were eligible for this retrospective analysis. All enrolled patients were treated with a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…A more objective measure than BCSR for evaluating neoadjuvant therapy is the proportion of patients whose lymph node status changes from positive to negative. Changes in lymph node status reflect the efficacy of a chemotherapeutic regimen and can greatly influence prognosis [47]. In the present study, the likelihood of negative lymph node status being achieved by the time of surgery was similar between the regimens in each of groups A and B.…”
Section: Secondary Endpointssupporting
confidence: 59%
“…A more objective measure than BCSR for evaluating neoadjuvant therapy is the proportion of patients whose lymph node status changes from positive to negative. Changes in lymph node status reflect the efficacy of a chemotherapeutic regimen and can greatly influence prognosis [47]. In the present study, the likelihood of negative lymph node status being achieved by the time of surgery was similar between the regimens in each of groups A and B.…”
Section: Secondary Endpointssupporting
confidence: 59%
“…Of the 12 studies, 10 studies reported OS and 11 reported DFS. With regard to the study area, four studies were conducted in Chinese ( 10 , 19 , 22 , 27 ), while the remaining nine studies were conducted in non-Chinese countries. The median follow-up ranged from 24 to 87 months.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 11 studies ( 9 , 10 , 18 22 , 24 27 ) examined the association between higher LNR and shorter OS of breast cancer patients after neoadjuvant chemotherapy. The results showed a significant association (HR: 4.77; 95%CI: 3.69–6.17; P < 0.001) with no heterogeneity ( I 2 = 41.6%; P = 0.072) ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations